2009
DOI: 10.1111/j.1743-6109.2008.01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Doxazosin and Sildenafil Exerts an Additive Relaxing Effect Compared with Each Compound Alone on Human Cavernosal and Prostatic Tissue

Abstract: Introduction Phosphodiesterase 5 inhibitors (PDE5) such as sildenafil are first-line treatment for erectile dysfunction (ED). Alpha1 (α1)-adrenoceptor antagonists such as doxazosin are indicated for the treatment of patients with lower urinary tract symptoms (LUTS)/benign prostatic hyperplasia (BPH). ED and LUTS/BPH are conditions that are often associated. Accordingly, α1-adrenoceptor antagonists and PDE5 inhibitors will be often prescribed in real life setting together. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 48 publications
4
32
0
1
Order By: Relevance
“…Increased adrenergic tonus also leads to enhanced expression of Rho-kinase pathway The presence of PDE-5 in the lower urinary tract of rats [Tinel et al 2006], the action of PDE-5i in the prostate muscles [Oger et al 2009[Oger et al , 2010 Angulo et al 2012] and clinical improvement of patients with LUTS/BPH using these drugs, which traditionally enable erection [Gacci et al 2012], demonstrated that, at least from a therapeutical point of view, ED and LUTS/BPH can be treated in the same manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased adrenergic tonus also leads to enhanced expression of Rho-kinase pathway The presence of PDE-5 in the lower urinary tract of rats [Tinel et al 2006], the action of PDE-5i in the prostate muscles [Oger et al 2009[Oger et al , 2010 Angulo et al 2012] and clinical improvement of patients with LUTS/BPH using these drugs, which traditionally enable erection [Gacci et al 2012], demonstrated that, at least from a therapeutical point of view, ED and LUTS/BPH can be treated in the same manner.…”
Section: Discussionmentioning
confidence: 99%
“…Oger and colleagues verified the action of sildenafil [Oger et al 2009] and of tadalafil [Oger et al 2010] in muscle fibers of human prostate and penile tissues, obtained from surgical specimens and observed that the two drugs have a relaxing effect in both tissues.…”
Section: Use Of the Same Medications To Simultaneously Treat Ed And Lmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Furthermore, an in vitro study has reported that such combination therapy relaxes human prostate smooth muscles more potently than monotherapy. 15 Mirodenafil ( is the most recently developed oral PDE5i and has been shown to be potent, reversible and selective. 16 In Korea, this drug has been commercially available since 2007.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Researchers also have found that a-adrenergic receptor antagonists potentiates corporal vasodilators dependent on cyclic nucleotide second-messengers. 28 Applying these findings to human models, Oger et al 29 used cavernosal and prostatic tissue specimens from patients who underwent penile or prostatic surgery and demonstrated that combining sildenafil with doxazosin in tissue baths significantly increased overall tissue relaxation. This discovery has been the impetus for several randomized studies attempting to demonstrate the efficacy and safety of combining PDE5Is with a-adrenergic receptor antagonists to treat complex ED ( Table 5).…”
Section: Pde5i Plus A-adrenergic Receptor Antagonistmentioning
confidence: 99%